The acceptance of a digital mammography system in a public hospital: Challenges and strategies applied in quality control tests (Research, Society and Development, 2023)
Objective: To evaluate the applicability of different protocols for conducting tests related to average glandular dose (AGD), automatic exposure control compensation (AEC), contrast-to-noise ratio (CNR), image uniformity, and artifacts. Methodology: PMMA phantoms were used to simulate the patient. Tests were performed in both STD and STD+ modes. In determining AGD, the phantoms were used to obtain technical exposure parameters. Air kerma was measured using a solid-state detector. In AEC compensation verification, regions of interest were marked in the acquired images. For CNR, a thin layer of contrast material (aluminum) was placed on one of the phantoms; regions of interest (ROIs) were marked in the contrast regions and background. For determining image uniformity, five ROIs were marked in the images. Results: AGD was in compliance in STD mode but exceeded tolerance in STD+ mode for two thicknesses (4 cm and 5 cm) of PMMA. Operating the equipment in STD+ mode resulted in a 57% increase in AGD for the 6 cm thickness and an improvement in the results for the 6 cm and 7 cm thicknesses in the CNR test. Only the 2.5 cm thick phantom exhibited uniformity as stipulated in IN 92. Conclusion: Patients with compressed breast thickness exceeding 7.5 cm are exposed to higher doses due to equipment limitations.